Extraction and antioxidant activities of broken Ganoderma lucidum spore - Senphan, T.; Takeungwongtrakul, S.; Kaewthong, P. (International Journal of Agricultural Technology, 2021)
Soxhlet and microwave-assisted extraction (MAE) methods showed the highest extraction yield and total phenolic content of extract from broken spores of Ganoiderma lucidum (p<0.05). However, the extraction time of MAE method was shorter than the soxhlet extraction method. The broken spores of G. Lucidum were extracted using different solvent types with MAE method. Ethanol extraction rendered extract with the highest total phenolic content and ferric reducing antioxidant power (FRAP) value (p<0.05). For metal chelating activity, ethanol and hexane extracts were significantly high compared to other extracts of broken G. lucidum spores (p<0.05). Thus, the use of appropriated extraction method and solvent type rendered to extract with high total phenolic content and antioxidant activities.